Value-based medicine as an opportunity for the Polish healthcare system in a post-pandemic reality on the example of selected health programs - Czerska, Iwona (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
The article aims to present the concept of value-based medicine (VBM) in the Polish health care system. The author reviewed the literature on the subject and formulated a research problem and two research questions to solve it. The issue of considering is health programs of the National Health Fund based on value. The author used professional scientific databases: Taylor & Francis online, PubMed, and Google Scholar to collect the bibliography. The literature on the subject covers mainly the years 2020–2022. First, the author presented the study’s theoretical framework by defining the EBM and VBM concepts, discussing the three main pillars of VBM, and highlighting its value limitations. Next, the author referred to the coronavirus pandemic and its impact on global health systems. The author characterized the current state of the health care system in Poland and listed its prospects for the post-pandemic future. Finally, the author presented three selected health programs based on the VBM model implemented in Polish healthcare: comprehensive coordinated care after myocardial infarction (KOS‑Zawał), POZ PLUS model, and comprehensive treatment of chronic wounds (KLRP-1 and KLRP-2). Of course, the discussed programs require further improvement and modification and may constitute the basis for developing other, new value-based programs. The value-based medicine model can complement the three branches of medicine — evidence-based, narrative, and integrative. Including these elements in the VBM model could benefit the entire health system, primarily medical staff and patients.
Keywords: value-based medicine; evidence-based medicine; healthcare system; post-pandemic reality; COVID-19 pandemic